Reassessing the fossil record of Lagostomus incisus Ameghino, 1888 (Rodentia, Caviomorpha) from the late Neogene of southern South America - Rasia, Luciano Luis (2021)
The extinct vizcacha Lagostomus incisus is a rodent recorded in Pliocene sediments of Buenos Aires Province (Argentina), including the montehermosan Monte Hermoso Formation and sediments bearing the “Irenean” Fauna, and the chapadmalalan Chapadmalal Formation. Its characteristic skull and cheek teeth anatomy permit to easily identify it even with fragmentary material. In this work, the fossil record of L. incisus is reassessed, being recognized in several units where it had not been reported before: the Unit 2 of the Saldungaray Formation, the Quequén Grande Local Fauna, and the Barker Formation in Buenos Aires Province (Argentina), and the San José Member of the Raigón Formation in Maldonado Department (Uruguay). These new records extend the distribution of L. incisus to most of central and southern Buenos Aires Province in Argentina and southern Uruguay. Additionally, the recent radiometric dates of some of the units with records of L. incisus permit to confidently limit the temporal range of this species to the late early–early late Pliocene.